ADMINISTRATION OF ACADEMIC PROGRAMMES AS A FACTOR OF UNIVERSITY MODERNIZATION - Andrey P. Klemeshev; Irina Yu. Kuksa (Высшее образование в России)
The article discusses how changes in the field of academic programmes administration affect other university activities. Among the key changes the authors mark out the following: shift from the chair system towards management of an academic programme; implementation of a module approach; training at the premises of resource centres providing professional field experience, as well as realization of network programmes; individualization and differentiation of educational paths; focus on an external customer of academic programmes; promotion of e-learning resources. In conclusion the influence of changes on the specific spheres of university activities is defined. These are administrative policy and human resource management, information infrastructure, material incentives for different categories of employees, as well as cooperation with employers.